2018
DOI: 10.1128/mbio.00559-18
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Pneumococcal Extracellular Vesicles on Cellular and Humoral Host Defenses

Abstract: Gram-positive bacteria, including the major respiratory pathogen Streptococcus pneumoniae, were recently shown to produce extracellular vesicles (EVs) that likely originate from the plasma membrane and are released into the extracellular environment. EVs may function as cargo for many bacterial proteins, however, their involvement in cellular processes and their interactions with the innate immune system are poorly understood. Here, EVs from pneumococci were characterized and their immunomodulatory effects inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(125 citation statements)
references
References 36 publications
6
111
0
3
Order By: Relevance
“…Synthetic peptide production, immunization, and validation by ELISA were done by Innovagen (Lund, Sweden), following a 41‐day immunization protocol including two booster injections. It was further used in previous studies (Codemo et al , ; Pathak et al , ). Detection of the GAPDH‐specific serum was performed using an anti‐rabbit secondary antibody (Thermo Fisher Scientific, cat# 31460).…”
Section: Methodsmentioning
confidence: 99%
“…Synthetic peptide production, immunization, and validation by ELISA were done by Innovagen (Lund, Sweden), following a 41‐day immunization protocol including two booster injections. It was further used in previous studies (Codemo et al , ; Pathak et al , ). Detection of the GAPDH‐specific serum was performed using an anti‐rabbit secondary antibody (Thermo Fisher Scientific, cat# 31460).…”
Section: Methodsmentioning
confidence: 99%
“…As isotype-switched IgG plays an important role in the fight against encapsulated extracellular bacteria (35, 36), antibodies (Abs) to the entire encapsulated SC19 strain were assessed after 2015033 immunization. Immunized mice exhibited a significant increase in IgG, IgG1, and IgG2a, which remained at high levels until the end of the experiment, while mice injected with phosphate buffered saline (PBS) showed no detectable increases (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies performed with different bacteria have suggested that, in addition to autolytic phenomena, eDNA might be associated with EV. Recent evidence indicates that S. pneumoniae , actively sheds extracellular nano-sized EV, as do many other microorganisms (3941). Whether pneumococcal EV contains DNA, however, was never examined.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the stability of EV under various conditions may vary and a vesicle that loses membrane integrity may ‘leak’ its constituents into the supernatant (vesicle destabilization), rather than break up, as reported in Bacillus anthracis , S. aureus and other microorganisms (61). Interestingly, a very recent study has reported that the LytA NAM-amidase is not needed for production of EV, although the presence of EV-associated DNA was not analyzed (41).…”
Section: Discussionmentioning
confidence: 99%